Bioatividade de plantas medicinais no controle de Sclerotinia isolado de Stevia rebaudiana (Bert.) Bertoni - Diniz, S. P S S [UNESP] (2005)
The microorganism Sclerotinia was isolated from roots of Stevia rebaudiana (Bert.) Bertoni in plantations in the northwest of Parana and submitted to the cultivation in the presence of extracts and vegetable balsams of Tarragon (Artemisia draconculus), Thyme (Thymus vulgaris), Manjerona (Origanum majorona), Mint citrata (Mintpiperita var. citrata), Purple Basil (Ocimum basilicum L.), Andiroba (Carapa guanensis) and Copaíba (Copaifera reticulata Ducke). The first five oils were extracted by steam drags, after the drying of the vegetable in greenhouse with circulation of air at 45°C. The last two were used in natura. A suspension (100ìl) of fungus previously cultivated, was added to each plate. The results show that after 7 days of incubation the thyme oils 10ìl, purple basil 25ìl, manjerona 25ìl, mint citrata 50ìl, tarragon 50ìl were capable to inhibit the growth of Sclerotinia, while the andiroba oil only reached this result with 200ìl. The copaiba balsam, even in the concentration of 500ìl, was unable to inhibit the growth of the microorganism.